Diagnóstico do saneamento básico de uma cidade de pequeno porte do Rio Grande do Norte – estudo de caso: Campo Grande-RN - Soares, Wilker Fernandes (Universidade Federal Rural do Semi-Árido, 2018)
Sanitation services are inseparable from the promotion of the quality of life of the population, the promotion and maintenance of environmental health and the protection of natural environments. The concern of the human being with basic sanitation has been present since the earliest civilizations. Currently, it is a right guaranteed by Federal Law nº 11.445 / 07, however, in order to bring universalization of these essential services to all communities, there is still a long effort to be developed. The main objective of this Course Conclusion Paper is to outline the profile of a small city in the state of Rio Grande do Norte in relation to basic sanitation, applying principles of the case study method in the municipality of Campo Grande, aiming to make a diagnosis to the in order to know its main deficiencies, potentialities, limitations and difficulties in the elaboration and execution of the Municipal Basic Sanitation Plan (PMSB), the main tool of strategies and guidelines in the formulation of public sector policies. It is also observed the perception of the population in relation to basic sanitation, considering its importance for the development of actions that deal with the studied subject. To do so, the most recent data available by the Brazilian Institute of Geography and Statistics (IBGE) and other official bodies were carried out, interviews were conducted with people who are part of the municipal sanitation, analyzes of documented information, field visits and a survey with the population of the city where the study was conducted. Thus, it was possible to verify that the municipality is not different from the majority of Brazilian municipalities, considered small, in the area of sanitation, presenting deficits in the sector of water supply and garbage collection and a almost nonexistence of sewage services and rainwater management.
Monografia
Keywords: Saneamento básico; Diagnóstico; Plano Municipal de Saneamento Básico; Participação social; Campo Grande/RN; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA